The EQ-5D (Euroqol) is a valid generic instrument for measuring quality of life in patients with dyspepsia. - Mahadeva, S.; Wee, H.; Goh, K.; Thumboo, J. (BMC, 2009)
The EQ-5D is an acceptable, valid and reliable generic instrument for measuring HRQOL in adult patients with dyspepsia.